Sistem Inventory Stok Onderdill Berbasis Web di PT. Bengawan Solo Trans - Yulia Mayasari; Donna Setiawati; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2021)
The process of inventory of goods and check item report at PT. Bengawan Solo Trans still uses the manual method, namely by recording in a ledger and inputting it into Microsoft Excel so that errors often occur that cause excess or lack of data so that they have to re-check and take a long time. Based on the results of the analysis in this study, the author uses the waterfall method while the tool used is UML (United Modelling Language). With this web-based inventory system, it can make it easier for logistics staff in the process of checking the number of stock items with one click.